Diagnosis and Treatment of Cerebral Syphilitic Gumma: A Report of Three Cases - Shao, Xuefei; Qiang, Di; Liu, Yinhua; Yuan, Quan; Tao, Jin; Ji, Bihua (Frontiers in Neuroscience, 2018)
Cerebral syphilitic gumma is very rare and is often pathologically confirmed following surgery. This study reports three patients with cerebral syphilitic gumma. The first case was a 62-year-old man who was admitted to our hospital due to speech arrest for 10 h. Head MRI showed a nodular signal shadow with a significant enhancement and a significant centerline shift. He subsequently received surgery, and cerebral syphilitic gumma was confirmed by postoperative pathology. The second patient was a 66-year-old man who was admitted to our hospital due to complaints of gradually decreasing right eye vision and headache for nearly 50 days. Enhanced MRI at admission indicated irregular clumping of high-signal mixed with low-signal foci on the frontal lobe. Subsequently, he was operatively treated and was confirmed to have cerebral syphilitic gumma by postoperative pathology. The third patient was a 37-year-old man who was admitted to our hospital due to dizziness for approximately 15 days. Head MRI indicated a slightly abnormal lamellar and longer T1, T2 signal shadow on the left side. He did not receive surgery, and his symptoms disappeared after anti-syphilitic treatment. Hence, we recommend a critical interpretation of preoperative imaging data, understanding the unique changes that arise in the brain that can be detected through imaging, and an analysis of the patient history and laboratory tests to re-evaluate the value of surgery, with the ultimate goal of performing a stabilizing treatment for cerebral syphilitic gumma.